2000
DOI: 10.1046/j.1365-2826.2000.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural Connections of Hypothalamic Neuroendocrine Nuclei in the Rat

Abstract: The secretion of many hormones, including oxytocin, vasopressin and growth hormone, is not constant but shows a day-night rhythm. The suprachiasmatic nucleus (SCN) is thought to generate most mammalian biological rhythms and previous studies have reported suprachiasmatic efferents to the paraventricular nucleus (PVN) and the supraoptic nucleus (SON). We used in vivo extracellular electrophysiological techniques to show that the SCN also sends direct and indirect neural projections to the arcuate nucleus (ARC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 42 publications
1
70
0
Order By: Relevance
“…Furthermore, electrophysiological analyses and anatomical studies have revealed the presence of neural connections between the Arc and the SCN that might contribute to feeding rhythms (47,59). More than 80% of both SCN and peri-SCN cells are responsive to Arc stimulation and ϳ13% of Arc cells contribute to the SCN/peri-SCN projection (76). Arc neurons contributing to this projection, some of which are sensitive to leptin, include POMC (42), galanin (2), and ghrelin (97).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, electrophysiological analyses and anatomical studies have revealed the presence of neural connections between the Arc and the SCN that might contribute to feeding rhythms (47,59). More than 80% of both SCN and peri-SCN cells are responsive to Arc stimulation and ϳ13% of Arc cells contribute to the SCN/peri-SCN projection (76). Arc neurons contributing to this projection, some of which are sensitive to leptin, include POMC (42), galanin (2), and ghrelin (97).…”
Section: Discussionmentioning
confidence: 99%
“…These include substantial direct (45) and indirect (32) afferent input to the dorsal shell of the SCN and the peri-SCN region from the VMN and the Arc. Electrophysiological analysis of the Arc projections to the SCN and peri-SCN region (71) have indicated that Ͼ 80% of both SCN and peri-SCN cells are responsive to Arc stimulation and that some projections are excitatory and others inhibitory. Antidromic analysis indicated ϳ13% of Arc cells contribute to the SCN/peri-SCN projection.…”
Section: Discussionmentioning
confidence: 99%
“…43) or ventral subperiventricular zone (38), knife-cut isolation of the SCN (81), MSG-induced destruction of the Arc (54), and MBH knife cuts (59,97) all reduce day-night differences in NREMS. These sites are reciprocally interconnected (6,71) and appear to form an afferent/ efferent loop, the integrity of which may be required for control of day-night distribution of REMS and NREMS.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, feeding behaviour undergoes the SCN-controlled circadian rhythm (Saeb-Parsy et al, 2000). Rodents eat during the dark phase of the circadian cycle and the expression of PK-2, in mouse SCN neurons, oscillates in a circadian manner and responds to light entrainment with a huge increase to signal the beginning of the 'circadian light period' (Cheng et al, 2002).…”
Section: Discussionmentioning
confidence: 99%